Improving Human Resource Quality and Cultural Values to Foster Community Independence in the Gayo Coffee Agrotourism Area, Bener Meriah Regency - Faisal, Rahmad; Ginting, Ginta; Asnawi, Said Kelana (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study aims to analyze the quality of human resources (HR), community culture, and economic independence in the Kopi Gayo Agrotourism area, Bener Meriah Regency, and how these factors contribute to community self-sufficiency. Using a mixed-method approach, the findings showed that the quality of HR in the area remains low, particularly in terms of knowledge, skills, and capabilities in managing coffee agritourism. Most respondents disagreed with the current quality, reflecting a limited understanding of the economic potential of coffee agritourism. The community's strong cultural value of gotong royong (mutual cooperation) has not been fully utilized in agritourism management because of a lack of coordination and collective awareness. Furthermore, the community's independence in facing competition and running agritourism businesses is low, as indicated by a lack of confidence and reluctance to innovate. This study recommends intensive training and continuous mentoring for the community, as well as strengthening local leadership to encourage collaboration. It is also suggested that the government and NGOs play an active role in improving access to information and global markets while also fostering more organized business groups. Enhancing HR quality, utilizing the gotong royong culture, and developing economic independence are key to improving community welfare in the Kopi Gayo Agrotourism area.